2010
DOI: 10.3390/ijerph7083115
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated to Endemic Dental Fluorosis in Brazilian Rural Communities

Abstract: The present paper examines the relationship between hydrochemical characteristics and endemic dental fluorosis, controlling for variables with information on an individual level. An epidemiological survey was carried out in seven rural communities in two municipalities in the state of Minas Gerais, Brazil. The Thystrup & Fejerskov index was employed by a single examiner for the diagnosis of dental fluorosis. A sampling campaign of deep groundwater in the rural communities of interest was carried out concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
(40 reference statements)
4
16
1
4
Order By: Relevance
“…Similarly, this has been observed in other countries, for instance, in a study performed in rural areas of Brazil was observed that children between 10 and 12 years and those between 13 and 15 years of age had greater chance of having severe dental fluorosis in comparison with the younger children and individuals aged between 16 and 22 years. [24] These results contrast to the study by Rwenyonyi et al . [25] who found significant increase in the severity of fluorosis with increasing age in a community with high concentration of fluoride in water.…”
Section: Discussioncontrasting
confidence: 70%
“…Similarly, this has been observed in other countries, for instance, in a study performed in rural areas of Brazil was observed that children between 10 and 12 years and those between 13 and 15 years of age had greater chance of having severe dental fluorosis in comparison with the younger children and individuals aged between 16 and 22 years. [24] These results contrast to the study by Rwenyonyi et al . [25] who found significant increase in the severity of fluorosis with increasing age in a community with high concentration of fluoride in water.…”
Section: Discussioncontrasting
confidence: 70%
“…5 Epidemiological surveys in Brazil have found a prevalence rate ranging from 3% to 80.4%. 4,6 In other countries, prevalence rates ranging from 15.8% 7 to 60.4% 8 have been reported. 8 Depending on its severity, DF may not only have esthetic consequences, but may also cause fracture, loss of enamel and pain, and may also adversely affect food choices, compromise chewing efficiency, and require complex dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is known that the prevalence and severity of DF is directly related to the amount of F ingested, age at the time of exposure and duration of exposure. 4 In contrast to the prevalence of dental caries, the prevalence of DF has increased worldwide. 5 Epidemiological surveys in Brazil have found a prevalence rate ranging from 3% to 80.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, other studies did not identify an association between fluorosis and sex, as in the communities 1 and 3 in this study (Sukhabogi et al, 2014;Ferreira et al, 2010). More research on the role of hormones and fluoride metabolism is required to elucidate this point.…”
Section: Discussionmentioning
confidence: 56%